1999
DOI: 10.1007/s002800050977
|View full text |Cite
|
Sign up to set email alerts
|

Drug retention and distribution after intratumoral chemotherapy with fluorouracil/epinephrine injectable gel in human pancreatic cancer xenografts

Abstract: In the human pancreatic cancer xenografts, i.t. administration of 5-FU/epi injectable gel provided significantly higher drug and/or metabolite concentrations for extended periods than was possible with either i.t. or i.p administration of drug solution. This i.t. drug delivery system could potentially be used to treat patients with pancreatic cancer to increase tumor exposure to drug and improve the therapeutic index in comparison to systemic drug administration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…The IT drug concentration was 9× higher using the IT gel vs. the IT drug solution. Even more interesting was the fact that IT injection of the drug solution resulted in 29× more drug in the tumor tissue compared to systemic drug delivery [70].…”
Section: Methods For Prolonging High Intratumoral Drug Concentrationmentioning
confidence: 99%
“…The IT drug concentration was 9× higher using the IT gel vs. the IT drug solution. Even more interesting was the fact that IT injection of the drug solution resulted in 29× more drug in the tumor tissue compared to systemic drug delivery [70].…”
Section: Methods For Prolonging High Intratumoral Drug Concentrationmentioning
confidence: 99%
“…Because of its biological properties and easy availability, it is widely used as a bio-material [2,3]. Collagen processing involves liquid aqueous preparations as injectables for tissue augmentation [4] or as drug carriers for tumor treatment [5] and tissue regeneration [6]. In many of these applications, the self assembly of collagen aggregation and organization of individual molecules play an important role.…”
Section: Introductionmentioning
confidence: 99%
“…Doxorubicin was most potent but all intratumoral systems reduced tumour burden by " 70% . In more recent research with¯uorouracil} epinephrine gel (Smith et al 1999), it was again shown that much higher concentrations were achieved in tumours for intratumoral gel injections (18.4 mm ) compared with¯uorouracil solutions given intravenously (2.02 mm ) or intraperitoneally (0.07 mm ). Ravichandran et al (1998) also showed the bene® t of intratumoral delivery of lithium linolenate for the treatment of pancreatic carcinoma in a nude mouse model.…”
Section: Animal Intratumoral Chemotherapy Studiesmentioning
confidence: 99%